Long term survival with thoracoscopic versus open lobectomy: propensity matched comparative analysis using SEER-Medicare database. (2nd October 2014) - Paul, Subroto; Isaacs, Abby J; Treasure, Tom; Altorki, Nasser K; Sedrakyan, Art
Abstract : Objective To compare long term survival after minimally invasive lobectomy and thoracotomy lobectomy. Design Propensity matched analysis. Setting Surveillance, Epidemiology and End Results (SEER)-Medicare database. Participants All patients with lung cancer from 2007 to 2009 undergoing lobectomy. Main outcome measure Influence of less invasive thoracoscopic surgery on overall survival, disease-free survival, and cancer specific survival. Results From 2007 to 2009, 6008 patients undergoing lobectomy were identified (n=4715 (78%) thoracotomy). The median age of the entire cohort was 74 (interquartile range 70-78) years. The median length of follow-up for entire group was 40 months. In a matched analysis of 1195 patients in each treatment category, no statistical differences in three year overall survival, disease-free survival, or cancer specific survival were found between the groups (overall survival: 70.6% v 68.1%, P=0.55; disease-free survival: 86.2% v 85.4%, P=0.46; cancer specific survival: 92% v 89.5%, P=0.05). Conclusion This propensity matched analysis showed that patients undergoing thoracoscopic lobectomy had similar overall, cancer specific, and disease-free survival compared with patients undergoing thoracotomy lobectomy. Thoracoscopic techniques do not seem to compromise these measures of outcome after lobectomy.